PENYULUHAN HIV/AIDS DAN BAHAYA NARKOBA PADA REMAJA SMA 1 KERAMBITAN KABUPATEN TABANAN PROVINSI BALI - I Made Sumawirawan; AA Intan Pramesti; Rendra Wisnu bistara; AA Lanang Ari Mayun; Gusti Ngurah Angga Nugraha (Bajang Institute, 2025)
Health Promotion has been conducted in the Senior High School at SMA 1 Kerambitan, Tabanan Regency, Province Bali. HIV AIDS prevention and NAFZA miss use as the primary topics given to the students on January 2025. 5 classes of the XII grade at SMA 1 erambitan, Tabanan as the subject contains more than 150 students.There was a very significant improvement in the students knowledge measured by quissionare questions that measured pre and post test health counseling. Knowledge improvement aproximately 70% after post test quitionare and its significant for the main purposed of this counseling.